Pengajaran Yesus Dalam Markus 10:17-22 Dan Implikasinya Bagi Formasi Rohani - Budiman, Sabda; Panggarra, Robi (Sekolah Tinggi Teologi Baptis Medan, 2024)
The story in Mark 10:17-22 is about a young man who came to Jesus and wanted to know how one can obtain eternal life. The problem is that nowhere does Jesus answer that to obtain eternal life, this rich young man must believe in Him. This is interesting and encourages the author to further examine Jesus' teaching from this narrative. The purpose of this study is to look at Jesus' teaching in Mark 10:17-22 and its implications for spiritual formation. The author used a qualitative method with a literature study approach related to the topic under study. The results of this study describe the teachings of Jesus, namely salvation is not obtained by doing good, believing and trusting in Jesus should not be accompanied by attachment to worldly things including possessions, and salvation is the grace of God. The implication for spiritual formation is that a person lives holy and does good not only by keeping silent, but also by doing real acts of kindness, and needs to be accompanied by humility.Keywords: spiritual formation, grace, wealth, young people